(untitled) (Revista Puertorriqueña de Psicologia, 2016)
Depression in teenagers is a serious mental health problem. The literature points out that affective disoreders in this population are more frequent that what was previously thought, which has led to moresystematic studies on that topic. Epidemiological research in Puerto Rico has established the prevalence rates to be 5.9% for this population. Although it is the third most frequent condition in Puerto Rican youngsters, research is almost nonexistent. The obective of this descriptive and qualitiative investigation was to explore from an international perspective the area(s) that young people identify as precipitators of depressive symptomatology. Sixty-seven therapeutic records of adolescents with depression were reviewed to identify the presenting problem(s). The results indicate that adolescents are able to identify the precipitating factors that permitted an interpersonal interpretation. The lack of interpersonal skills, followed by interpersonal disputes or conflicts were the most frequent problems. The implications of these results for the treatment and prevention of juvenile depression are discussed.